Photodynamic Effects of Zinc(II) Phthalocyanine-Loaded Polymeric Micelles in Human Nasopharynx KB Carcinoma Cells - Garcia Vior, María Cecilia (2013)
A major difficulty in photodynamic therapy is the poor solubility of the photosensitizer (PS) under physiological conditions which correlates with low bioavailability. PS aggregation leads to a decrease in the photodynamic efficiency and a more limited activity in vitro and in vivo. To improve the aqueous solubility and reduce the aggregation of 2,9(10),16(17),23(24)-tetrakis[(2-dimethylamino)ethylsulfanyl] phthal-ocyaninatozinc(II) (Pc9), the encapsulation into four poloxamine polymeric micelles (T304, T904, T1107 and T1307) displaying a broad spectrum of molecular weight and hydrophilic–lipophilic balance was investigated. The aqueous solubility of Pc9 was increased up to 30 times. Morphological evaluation showed the formation of Pc9-loaded spherical micelles in the nanosize range. UV/Vis and fluorescence studies indicated that Pc9 is less aggregated upon encapsulation in comparison with Pc9 in water–DMSO 2% and remained photostable. Pc9-loaded micelles generated singlet molecular oxygen in high yields. Photocytotoxicity assays using human nasopharynx KB carcinoma cells confirmed that the encapsulation of Pc9 in T1107 and T1307 increases its photocytotoxicity by 10 times in comparison with the free form in water–DMSO. In addition, Pc9 incorporated into cells was mainly localized in lysosomes.